PENGARUH LARGE POSITIVE ABNORMAL BOOK-TAX DIFFERENCES TERHADAP PERSISTENSI LABA - Rachmawati, Nurul Aisyah; Martani, Dwi (Jurnal Akuntansi dan Keuangan Indonesia, 2014)
The purpose of this study is to analyze the effect of Large Positive Abnormal Book-Tax Differences (LPABTD) on earnings persistence and accruals persistence. This study used unbalanced panel data of listed companies in Indonesia Stock Exchange from 2006-2011. It is hypothesized that firms with LPABTD exhibit lower earnings and accruals persistence than other firms with Large Positive Normal Book-Tax Differences (LPNBTD). The results provide evidence which is consistent with the hypotheses. It is shown that firms with LPABTD exhibit lower earnings quality than other firms with LPNBTD.